Grandparenting in rural China: A culture-centered approach (CCA) to understand economic inequality and rural labor change. (May 2022) - Sun, Kang; Dutta, Mohan
The large-scale rural-to-urban migration in China has resulted in separated families and left-behind family members in the countryside. Various socioeconomic changes took place in rural China's daily life due to migration, which provides unique perspectives to understand the hidden costs of the national discourse on development. This study aims to reveal how rural grandparenting resulted from the uneven economic development between a Chinese city and a village. A dual-site ethnographic study was conducted in one Northern village and one Southern city. Interviews, focus groups, and participant observation were used to form methodological triangulation to understand how socioeconomic features have made grandparenting necessary. Instead of focusing only on grandparents' daily responsibilities of taking care of their grandchildren, we compared grandparents' and parents' views on the changes in grandparents' socioeconomic roles, feelings of loneliness, and economic independence, as well as grandchildren's socialization processes. The study showcases grandparenting as having a social significance larger than being individualized acts of family care.